Reflection on Effective English Language Teaching and Learning Methodologies in Higher Education: Identifying Sources of University Teachers’ Beliefs and Requirements for Improvement - Alnajami, Mai Lutfi (Psycho-Educational Research Reviews, 2019)
The purpose of carrying this study is to examine the university teachers’ beliefs concerning effective English Language Teaching and Learning Methodologies in higher education, the potential sources of the university teachers’ beliefs concerning effective English Language Teaching and Learning Methodologies in higher education, as well as the main requirements for improving effective English Language Teaching and Learning Methodologies in higher education. Key participants in purposeful sampling consist of fifty (50) university teachers (4 assistant professors, 16 lecturers, and 30 language teachers) from the English Language Institute, University of Jeddah. All the participants had a teaching experience of 3-6 and above. An eight-question semi-structured interview and a seventeen, three-point opinion survey statement survey were administered to the participants. The findings of this study indicated that there are four identified themes, namely the university teachers own experience as language learners, Experience of what works best in their classes, Teaching methods, and Established practice. It was found that new methods of teaching English at the university level are crucial. Additionally, motivating students, trusting their abilities, and caring of them are required. Moreover, university teachers should take their professional development into consideration. This will be through conducting research in this field of specialty. Lastly, there should be a rapport between and among university teachers and their students.